Impact of Milling on Rice Constituents (Oryza Sativa L.): A Metabolomic Approach. (2nd November 2017) - Lim, Dong Kyu; Long, Nguyen Phuoc; Choo, Sanghan; Mo, Changyeun; Dong, Ziyuan; Kim, Giyoung; Kwon, Sung Won
ABSTRACT: Milling is an influential factor that affects the nutritional components in rice. However, the alteration of rice constituents by milling has not been thoroughly examined. In this study, rice with various degrees of milling was analyzed by gas chromatography–mass spectrometry and high-performance liquid chromatography–mass spectrometry. Principal component analysis and partial least square-discriminant analysis were performed to characterize the nutritional components that have significant changes during milling. The concentrations of sugars and sugar alcohols decreased while the phospholipids increased in accordance with the milling degree. These results provide a contrast to the common idea that brown rice is nutritionally superior to white rice. In conclusion, the knowledge of nutritional alterations related to milling may benefit rice production and consumption.